Pengaruh Adversity Quotient Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Di SMP - Nurrahmi, Dwi; Setiani, Yani; Santosa, Cecep Anwar Hadi Firdos (International Journal of Education, Information Technology, and Others, 2025)
This research is to determine the effect of the adversity quotient on students' mathematical problem solving abilities. This research was conducted at SMP Negeri 17 Kota Serang class VII.The type of research used is expost facto. A sample of sixty three seven grade students was taken using simple random sampling techniques.The data analysis used is the linearity test,regression significance test, and simple regression. Data collection is done by giving tests and questionnaires. The research results show that there are a There is a significant influence between Adversity Quotient on mathematical problem solving abilities and the influence of Adversity Quotient is 17.1%. students' mathematical problem solving abilities, the rest is beyond learning independence factor.